Pemberdayaan Kelompok Lanjut Usia melalui Pengenalan Teknologi Pembuatan Pupuk Organik Cair (POC) sebagai Upaya Bentuk Kepedulian terhadap Lingkungan - Kasmawan, I Gde Antha; Sutapa, Gusti Ngurah; Yuliara, I Made (Bumi Lestari; Vol 17 No 2 (2017), 2017)
In order to avoid post power syndrome, the elderly who have a hobby of farming / gardening can be empowered through the introduction of LOF (liquid organic fertilizer) making technology and its application. The aim is for the elderly to understand the technology of making organic fertilizers that are lightweight, useful and entertaining as well as for them to feel contribute in maintaining the environment. The training method applied is a combination of interactive lecture and practice methods. Based on these methods, have succeeded in growing their creativity in making LOF and feel comforted on the results obtained. Successful LOF products contained nitrogen, phosphorus and potassium (NPK) of 146,701 mg / L, 0.741 mg / L, and 0.035 mg / L, respectively, and magnesium (Mg) and calcium (Ca) of 86.332 mg / L and 1.970 mg / L. The application of LOF products has been done on the orchid plants ( Phalaenopsis amabilis ) with satisfactory results. Thus, the mastery of LOF making technology and its application will reduce the dependence of chemical fertilizer use and replace it with homemade organic fertilizer so it can contribute in maintaining health and environmental sustainability.